A UV-heat dual-curing electronic adhesive and preparation method thereof
By introducing the groups required for subsequent thermal curing reactions into the electronic adhesive, double curing of ultraviolet light-thermal curing is achieved, solving the problem of incomplete ultraviolet light curing, reducing contamination on electronic components, and improving curing efficiency and mechanical properties.
Patent Information
- Application Number
- CN202411641449.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing ultraviolet curing electronic adhesives are not cured completely in the ultraviolet shadowed area, resulting in low adhesive performance and contamination of electronic components. Small molecular catalysts are required during thermal curing, which may cause harm to electronic components.
UV-thermal curing electronic adhesive is used to introduce carboxyl and tertiary amine groups required for subsequent thermal curing reactions into acrylic modified epoxy resin, which avoids the need for additional curing agents or catalysts for thermal curing reactions. .
Complete curing in the shadowed area of ultraviolet light is achieved, contamination on electronic components is reduced, and the efficiency of the curing process and the mechanical properties of the adhesive are improved.
Smart Images

Figure CN119119937B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic polymer adhesives, and in particular to an ultraviolet light-heat dual-curing electronic adhesive and a preparation method thereof. Background Art
[0002] During the manufacturing process of electronic display devices, the frame and electronic components block the screen components or electronic circuit boards, resulting in insufficient UV exposure in this area, incomplete curing of the electronic optical adhesive, and the adhesive bonding performance of the adhesive is lower than the standard requirements. In addition, uncured small molecule compounds will spontaneously migrate, contaminate or corrode electronic components, affect the clarity and resolution of electronic displays, increase the defective rate of products, and shorten their service life.
[0003] In order to solve the problem of incomplete curing of UV-curable electronic adhesives in the UV shadow area, UV-moisture or UV-heat dual-curing adhesives are often used. For the UV-moisture dual-curing process, UV curing is first used to initiate free radical polymerization of monomers containing carbon-carbon double bonds, so that the adhesive quickly loses fluidity and sets; the monomers that are not completely reacted in the shadow area undergo polymerization with moisture (water molecules) in the environment (without UV initiation), eliminating the harm of unreacted monomers to electronic products. However, the moisture curing reaction time is affected by the ambient humidity (i.e., the content of water molecules in the environment). In general, in order to reduce the impact of water molecules in the environment on electronic components, the manufacturing workshop of electronic display devices strictly controls the air humidity, resulting in a low content of water molecules in the environment and a long subsequent moisture curing cycle. Inadequately cured electronic products need to be placed in the production workshop or warehouse for a long time (for moisture curing), which reduces the utilization rate of the production workshop or warehouse and prolongs the delivery time. Switching to the UV-heat dual-curing process can improve production efficiency and yield rate. First, the adhesive is cured by UV curing reaction, and then heating is used to initiate a chemical reaction, so that the unreacted monomers or functional groups in the UV shadow area react completely. However, in the subsequent thermal reaction, a small molecule catalyst (peroxide or tertiary amine compound) is often added for excitation. The thermal reaction exciter peroxide generates small molecule fragments after thermal decomposition, and the tertiary amine catalyst itself is a small molecule compound, which has potential damage to the yield and service life of electronic components. Summary of the invention
[0004] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and provide a UV-heat dual-curing electronic adhesive and a preparation method thereof, which does not require the addition of an additional curing agent or catalyst for a thermal curing reaction. The molecular chain of the UV-induced free radical polymerization product contains a carboxyl group (reacting with an epoxy group) and a tertiary amine group (catalyzing a thermal curing reaction) required for a subsequent thermal curing reaction, thereby reducing contamination of electronic components at the source.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The first object of the present invention is to provide a UV-heat dual-curing electronic adhesive, which comprises the following components in parts by weight: 45.0 to 65.0 parts of acrylic modified epoxy resin, 7.0 to 10.0 parts of N,N-dimethylallylamine, 3.0 to 5.0 parts of methacrylic acid, 5.0 to 10.0 parts of glycidyl methacrylate, 20.0 to 30.0 parts of ethoxyethyl methacrylate, 1.0 to 3.5 parts of free radical photoinitiator, and 0.01 to 0.05 parts of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid;
[0007] The acrylic acid modified epoxy resin is synthesized from methacrylic acid, difunctional glycidyl ether, triphenylphosphine and a polymerization inhibitor.
[0008] Furthermore, the preparation method of the acrylic acid-modified epoxy resin comprises the following steps:
[0009] S1, adding methacrylic acid and difunctional glycidyl ether according to a preset molar ratio, and then adding triphenylphosphine and a polymerization inhibitor, and mixing them evenly;
[0010] S2. Heat to 120-130°C under nitrogen and stirring conditions, react for 3-8 hours until the acid value of the product is ≤10mgKOH / g, cool down, filter, and obtain acrylic acid-modified epoxy resin.
[0011] Furthermore, the preset molar ratio is (1.03~1.05):1.
[0012] Furthermore, the amount of triphenylphosphine added is 0.3% to 0.35% based on the total mass of methacrylic acid and difunctional glycidyl ether.
[0013] Furthermore, the amount of the polymerization inhibitor added is 0.01% to 0.05% based on the total mass of methacrylic acid and difunctional glycidyl ether.
[0014] Furthermore, the difunctional glycidyl ether is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A resin, 1,4-butanediol glycidyl ether, neopentyl glycol diglycidyl ether or 1,6-hexanediol diglycidyl ether.
[0015] Furthermore, the polymerization inhibitor is any one or more of hydroquinone, p-hydroxyanisole, p-benzoquinone or p-methylhydroquinone.
[0016] Furthermore, the free radical photoinitiator is any one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide or ethyl 2,4,6-trimethylbenzoylphenylphosphonate.
[0017] Furthermore, in the infrared absorption spectrum of the acrylic modified epoxy resin, there are absorption peaks derived from the stretching vibration of a hydroxyl group, an absorption peak derived from the stretching vibration of a carbonyl group, an absorption peak derived from the stretching vibration of a vinyl group, and an absorption peak derived from the stretching vibration of an epoxy group.
[0018] Furthermore, the number average molecular weight of the polymerized product of the electronic adhesive after ultraviolet light treatment is 2000-3000 g / mol.
[0019] The second object of the present invention is to provide a method for preparing a UV-heat dual-curing electronic adhesive, comprising adding 45.0 to 65.0 parts of an acrylic acid-modified epoxy resin, 7.0 to 10.0 parts of N,N-dimethylallylamine, 3.0 to 5.0 parts of methacrylic acid, 5.0 to 10.0 parts of glycidyl methacrylate, 20.0 to 30.0 parts of ethoxyethyl methacrylate, 1.0 to 3.5 parts of a free radical photoinitiator, and 0.01 to 0.05 parts of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid into a container in sequence, and mixing well to obtain the adhesive.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention does not require the addition of a curing agent or catalyst for a thermal curing reaction. The molecular chain of the ultraviolet light-induced free radical polymerization product (number average molecular weight 2000-3000 g / mol) contains carboxyl groups (reacting with epoxy groups) and tertiary amine groups (catalyzing thermal curing reactions) required for the subsequent thermal curing reaction. Therefore, there is no need to add small molecule compounds such as curing agents or catalysts to the electronic adhesive, which reduces the pollution to electronic components at the source;
[0022] (2) The residual monomers from the UV-induced free radical polymerization can be subsequently polymerized by heat, eliminating the possibility of residual methacrylate small molecule monomers and contamination of electronic components;
[0023] (3) The curing process has high reaction efficiency, fast curing and little impact from the environment;
[0024] (4) The addition of a chain transfer agent to the formula provided by the present invention effectively controls the molecular weight of the UV-polymerized product, and the cross-linked network generated by subsequent thermal curing is uniform, and the mechanical properties of the adhesive are good. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1This is the infrared spectrum of the acrylic acid-modified bisphenol A epoxy resin obtained in Example 1;
[0026] Figure 2 is the gel permeation chromatography curve of the UV-polymerized product of Example 1;
[0027] Figure 3 The thermal curing DSC curve of the electronic adhesive prepared with the resin obtained in Example 1;
[0028] Figure 4 The tensile properties of the UV-heat dual-curing electronic adhesive obtained in Example 1;
[0029] Figure 5 The infrared spectrum curve of the modified epoxy resin obtained in Example 2;
[0030] Figure 6 The thermal curing DSC curve of the electronic adhesive prepared with the resin obtained in Example 2;
[0031] Figure 7 The tensile properties of the UV-heat dual-curing electronic adhesive obtained in Example 2. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention clearer, embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0033] The reagents and experimental materials used in the present invention can be obtained commercially.
[0034] The tensile property test method in this embodiment is as follows: the electronic adhesive product is poured into a polytetrafluoroethylene mold with a length of 35 mm, a width of 6 mm, and a depth of 1.5 mm, and irradiated with a 1000W mercury lamp (wavelength of 350-450nm) for 10 minutes. Then, the mold is placed in a 140°C oven for curing for 3 hours. The tensile curve of the sample is measured with a universal tensile machine, and the crossbeam displacement speed is 1 mm / min.
[0035] Example 1
[0036] A UV-heat dual-curing electronic adhesive comprises the following components in parts by weight:
[0037] 45 parts of acrylic modified epoxy resin, 10.0 parts of N,N-dimethylallylamine, 5.0 parts of acrylic acid, 10.0 parts of glycidyl methacrylate, 30.0 parts of ethoxyethyl methacrylate, 3.5 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and 0.05 parts of 2-(dodecyltrithiocarbonate)-2-methylpropionic acid.
[0038] After weighing the above components according to the weight composition, add them into a single-mouth round-bottom flask and dilute them evenly with 1.5 times the mass of 1,4-dioxane. Irradiate with ultraviolet light for 3 hours under nitrogen atmosphere, stirring and room temperature. The obtained product is condensed with a rotary evaporator and precipitated in anhydrous methanol. Collect the solid precipitate and dry it in a vacuum oven at 30°C to constant weight to obtain a light yellow powder with a yield of 87.3%.
[0039] Wherein, the preparation of acrylic acid modified epoxy resin:
[0040] 3.71 g (0.0515 mol) acrylic acid, 9.51 g (0.050 mol) bisphenol A epoxy resin (epoxy value 0.526 eq / 100 g), 0.04 g triphenylphosphine and 6.6 mg hydroquinone were added to a 50 ml reaction bottle. Under nitrogen protection and stirring conditions, the mixture was heated to 120 ° C and reacted for 8 h. The acid value of the product was measured to be 8.6 mgKOH / g. The product was obtained by cooling and filtering.
[0041] like Figure 1 The infrared spectrum of acrylic modified epoxy resin is shown in Figure 2. -1 The absorption peak at 1729 cm is the characteristic peak of -OH generated after epoxy ring opening (due to the hydrogen bond interaction between -OH and carboxyl groups, the peak here is wider than the absorption peak of pure -OH). -1 The absorption peak that appears is the characteristic peak of C=O, at 1635 cm -1 、809 cm -1 The absorption peak at 911 cm -1 The absorption peak appearing at is the characteristic peak of the epoxy group in the product, indicating that the target product, acrylic acid-modified epoxy resin, was successfully synthesized.
[0042] like Figure 2The figure shows the gel permeation chromatography curve of the UV polymerization product. With tetrahydrofuran as the eluent and PS as the standard, the average molecular weight and distribution of the product were determined by gel permeation chromatography (the measurement temperature was 40°C). As can be seen from the figure, the molecular weight of the UV-initiated free radical polymerization product is about 2130 g / mol, and the molecular weight distribution coefficient is 1.42 (the molecular weight distribution of the UV polymerization product is narrow). It shows that adding a chain transfer agent to the UV polymerization raw material effectively controls the molecular weight of the UV polymerization product, which is convenient for the subsequent thermal curing reaction.
[0043] like Figure 3 As shown, it is the thermal curing DSC curve of the electronic adhesive obtained in Example 1. The electronic adhesive starts to react at 129.8°C and reaches the highest reaction rate at 179.7°C.
[0044] like Figure 4 As shown in FIG. 1 , it is a tensile performance diagram of the electronic adhesive obtained in Example 1. Figure 4 It can be seen that its tensile strength is 17.3 MPa, which is higher than the tensile strength of the sample without chain transfer agent under the same conditions, which is 15.8 MPa. This shows that the sample with chain transfer agent has a more uniform cross-linking structure and relatively better mechanical properties.
[0045] The rubber block after the tensile test was weighed on a 1 / 10,000 balance, then wrapped with qualitative filter paper and placed in a Soxhlet extractor, and extracted with dichloromethane for 24 hours. The sample after solvent extraction was placed in a 50°C oven and dried for 12 hours. The weight of the sample did not decrease when weighed on a 1 / 10,000 balance. This indicates that there are no small molecules remaining in the cured electronic adhesive.
[0046] Example 2
[0047] A UV-heat dual-curing electronic adhesive comprises the following components in parts by weight:
[0048] 65 parts of acrylic modified epoxy resin, 7.0 parts of N,N-dimethylallylamine, 3.0 parts of methacrylic acid, 5.0 parts of glycidyl methacrylate, 20.0 parts of ethoxyethyl methacrylate, 1.0 part of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 0.01 part of 2-(dodecyltrithiocarbonate)-2-methylpropionic acid.
[0049] After weighing the above components according to the weight composition, add them into a single-mouth round-bottom flask and dilute them evenly with 1.5 times the mass of 1,4-dioxane. Irradiate with ultraviolet light for 3 hours under nitrogen atmosphere, stirring and room temperature. The obtained product is condensed with a rotary evaporator and precipitated in anhydrous methanol. Collect the solid precipitate and dry it in a vacuum oven at 30°C to constant weight to obtain a light yellow powder with a yield of 81.6%.
[0050] Wherein, the preparation of acrylic acid modified epoxy resin:
[0051] 4.44 g (0.0516 mol) of methacrylic acid, 10.81 g (0.050 mol) of neopentyl glycol diglycidyl ether, 0.05 g of triphenylphosphine and 1.5 mg of p-hydroxyanisole were added to a 50 ml reaction bottle. Under nitrogen protection and stirring conditions, the mixture was heated to 130 °C and reacted for 3 h. The acid value of the product was measured to be 9.7 mgKOH / g. The product was obtained by cooling and filtering.
[0052] like Figure 5 The infrared spectrum of the acrylic modified epoxy resin obtained in Example 2 is shown in FIG. -1 The absorption peak at 1730 cm-1 is the characteristic peak of -OH generated after epoxy ring opening (due to the hydrogen bond interaction between -OH and carboxyl groups, the peak here is wider than the absorption peak of pure -OH). -1 The absorption peak that appears is the characteristic peak of C=O, at 1634 cm -1 、810 cm -1 The absorption peak at 912 cm -1 The absorption peak appearing at is the characteristic peak of the epoxy group in the product, indicating that the target product was successfully synthesized.
[0053] like Figure 6 The figure shows the gel permeation chromatography curve of the UV polymerization product. With tetrahydrofuran as the eluent and PS as the standard, the average molecular weight and distribution of the product were determined by gel permeation chromatography (the measurement temperature was 40°C). As can be seen from the figure, the molecular weight of the UV-initiated free radical polymerization product is about 2790 g / mol, and the molecular weight distribution coefficient is 1.57. It shows that adding a chain transfer agent to the UV polymerization raw material effectively controls the molecular weight of the UV polymerization product, which is beneficial to controlling the uniformity of the cross-linked network structure.
[0054] like Figure 7 As shown in FIG. 2 , it is a tensile performance diagram of the electronic adhesive obtained in Example 2. Figure 4 It can be seen that the tensile strength of the electronic adhesive is 15.8 MPa, which is higher than the tensile strength of the sample without chain transfer agent under the same conditions (13.1 MPa). This shows that the sample with chain transfer agent has a more uniform cross-linking structure and relatively better mechanical properties.
[0055] The rubber block after the tensile test was weighed on a 1 / 10,000 balance, then wrapped with qualitative filter paper and placed in a Soxhlet extractor, and extracted with dichloromethane for 24 hours. The sample after solvent extraction was placed in a 50°C oven and dried for 12 hours. The weight of the sample did not decrease when weighed on a 1 / 10,000 balance. This indicates that there are no small molecules remaining in the cured electronic adhesive.
[0056] Example 3
[0057] A UV-heat dual-curing electronic adhesive comprises the following components in parts by weight:
[0058] 55 parts of acrylic modified epoxy resin, 8.5 parts of N,N-dimethylallylamine, 4.0 parts of methacrylic acid, 7.5 parts of glycidyl methacrylate, 25.0 parts of ethoxyethyl methacrylate, 1.0 part of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 1.0 part of 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and 0.35 part of 2-(dodecyltrithiocarbonate)-2-methylpropionic acid.
[0059] After weighing the above components according to the weight composition, add them into a single-mouth round-bottom flask and dilute them evenly with 1.5 times the mass of 1,4-dioxane. Irradiate with ultraviolet light for 3 hours under nitrogen atmosphere, stirring and room temperature. The obtained product is condensed with a rotary evaporator and precipitated in anhydrous methanol. Collect the solid precipitate and dry it in a vacuum oven at 30°C to constant weight to obtain a light yellow powder with a yield of 85.5%.
[0060] Wherein, the preparation of acrylic acid modified epoxy resin:
[0061] 4.44 g (0.0516 mol) of methacrylic acid, 6.49 g (0.030 mol) of neopentyl glycol diglycidyl ether, 4.05 g of 1,4-butanediol diglycidyl ether (0.020 mol), 0.05 g of triphenylphosphine and 1.5 mg of p-benzoquinone were added to a 50 ml reaction bottle. Under nitrogen protection and stirring conditions, the above mixture was heated to 125 ° C and reacted for 5.5 h. The acid value of the product was measured to be 7.8 mgKOH / g. The product was obtained by cooling and filtering.
[0062] The acrylic modified epoxy resin obtained in Example 3 was subjected to infrared spectroscopy analysis. The structure was similar to that of the acrylic modified epoxy resin prepared in Example 1, and had absorption peaks derived from the stretching vibration of the hydroxyl group, the stretching vibration of the carbonyl group, the stretching vibration of the vinyl group, and the stretching vibration of the epoxy group, indicating that the target product was successfully synthesized.
[0063] The average molecular weight and distribution of the UV-polymerized product were determined by gel permeation chromatography (measurement temperature was 40°C) using tetrahydrofuran as eluent and PS as standard. The molecular weight of the UV-initiated free radical polymerization product was about 2820 g / mol, and the molecular weight distribution coefficient was 1.58. This indicates that adding a chain transfer agent to the UV-polymerized raw material effectively controls the molecular weight of the UV-polymerized product, which is beneficial to controlling the uniformity of the cross-linked network structure.
[0064] The tensile properties of the electronic adhesive obtained in Example 3 were tested, and the tensile strength of the electronic adhesive was 16.1 MPa.
[0065] The rubber block after the tensile test was weighed on a 1 / 10,000 balance, then wrapped with qualitative filter paper and placed in a Soxhlet extractor, and extracted with dichloromethane for 24 hours. The sample after solvent extraction was placed in a 50°C oven and dried for 12 hours. The weight of the sample did not decrease when weighed on a 1 / 10,000 balance. This indicates that there are no small molecules remaining in the cured electronic adhesive.
[0066] Example 4
[0067] A UV-heat dual-curing electronic adhesive comprises the following components in parts by weight:
[0068] 58 parts of acrylic acid modified bisphenol F epoxy resin, 9.0 parts of N,N-dimethylallylamine, 1.0 parts of methacrylic acid, 3.0 parts of acrylic acid, 6.5 parts of glycidyl methacrylate, 27.0 parts of ethoxyethyl methacrylate, 1.0 parts of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 1.5 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 1.0 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and 0.015 parts of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid. The preparation method of the electronic adhesive is basically the same as that of Example 1.
[0069] The tensile properties of the electronic adhesive obtained in Example 4 were tested, and the tensile strength of the electronic adhesive was 15.3 MPa.
[0070] Example 5
[0071] A UV-heat dual-curing electronic adhesive comprises the following components in parts by weight:
[0072] 60 parts of acrylic acid-modified hydrogenated bisphenol A epoxy resin, 8.5 parts of N,N-dimethylallylamine, 2.0 parts of methacrylic acid, 2.0 parts of acrylic acid, 9.5 parts of glycidyl methacrylate, 26.0 parts of ethoxyethyl methacrylate, 1.0 parts of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 0.5 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and 0.02 parts of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid. The preparation method of the electronic adhesive is basically the same as that of Example 1.
[0073] The tensile properties of the electronic adhesive obtained in Example 5 were tested, and the tensile strength of the electronic adhesive was 16.7 MPa.
[0074] Example 6
[0075] A UV-heat dual-curing electronic adhesive comprises the following components in parts by weight:
[0076] 30 parts of acrylic acid modified bisphenol A epoxy resin, 20 parts of acrylic acid modified 1,4-butanediol glycidyl ether, 5 parts of methacrylic acid modified 1,6-hexanediol glycidyl ether, 10.0 parts of N,N-dimethylallylamine, 3.0 parts of acrylic acid, 0.5 parts of methacrylic acid, 5.5 parts of glycidyl methacrylate, 24.0 parts of ethoxyethyl methacrylate, 2.0 parts of 2,4,6-trimethylbenzoyl diphenyl phosphine oxide, 1.0 parts of phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, and 0.04 parts of 2- (dodecyl trithiocarbonate) -2-methylpropionic acid. The preparation method of the electronic adhesive is basically the same as that of Example 1.
[0077] The tensile properties of the electronic adhesive obtained in Example 6 were tested, and the tensile strength of the electronic adhesive was 14.5 MPa.
[0078] Example 7
[0079] A UV-heat dual-curing electronic adhesive comprises the following components in parts by weight:
[0080] 15 parts of methacrylic acid modified hydrogenated bisphenol A epoxy resin, 40 parts of acrylic acid modified 1,6-hexanediol diglycidyl ether, 5 parts of acrylic acid modified bisphenol F epoxy resin, 8.0 parts of N,N-dimethylallylamine, 3.0 parts of acrylic acid, 6.5 parts of glycidyl methacrylate, 30.0 parts of ethoxyethyl methacrylate, 1.0 parts of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 0.5 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide or 1.5 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and 0.045 parts of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid. The preparation method of the electronic adhesive is basically the same as that of Example 1.
[0081] The tensile properties of the electronic adhesive obtained in Example 7 were tested, and the tensile strength of the electronic adhesive was 15.8 MPa.
[0082] Comparative Example 1
[0083] The method is basically the same as Example 1, except that the chain transfer agent 2-(dodecyl trithiocarbonate)-2-methylpropionic acid is not added. The tensile strength of the electronic adhesive prepared is 15.8 MPa.
[0084] Comparative Example 2
[0085] The method is basically the same as Example 2, except that the chain transfer agent 2-(dodecyl trithiocarbonate)-2-methylpropionic acid is not added. The tensile strength of the prepared electronic adhesive is 13.1 Mpa.
[0086] Comparative Example 3
[0087] The process is basically the same as Example 3, except that the chain transfer agent 2-(dodecyl trithiocarbonate)-2-methylpropionic acid is not added.
[0088] 55 parts of acrylic modified epoxy resin, 8.5 parts of N,N-dimethylallylamine, 4.0 parts of methacrylic acid, 7.5 parts of glycidyl methacrylate, 25.0 parts of ethoxyethyl methacrylate, 1.0 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and 1.0 parts of 2,4,6-trimethylbenzoyldiphenylphosphine oxide were weighed and added to a single-mouth round-bottom flask, and diluted evenly with 1.5 times the mass of 1,4-dioxane. Under nitrogen atmosphere, stirring and room temperature, irradiate with ultraviolet light for 3 hours. The obtained product was condensed with a rotary evaporator and precipitated in anhydrous methanol. The solid precipitate was collected and dried in a vacuum oven at 30°C to constant weight to obtain a white powder with a yield of 84.4%. The molecular weight of the product was determined by gel permeation chromatography to be 5610 g / mol, and the molecular weight distribution coefficient was 2.18. The tensile properties of the electronic adhesive prepared in the above steps were tested, and the tensile strength of the electronic adhesive was 11.88 MPa. The reason may be that the cross-linked network generated by the cured product is uneven.
[0089] For matters not mentioned above, the prior art applies.
[0090] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make modifications or supplements to the described specific embodiments or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above implementations based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A UV-heat dual-curing electronic adhesive, characterized in that: The invention comprises the following components in parts by weight: 45.0 to 65.0 parts of acrylic modified epoxy resin, 7.0 to 10.0 parts of N,N-dimethylallylamine, 3.0 to 5.0 parts of methacrylic acid, 5.0 to 10.0 parts of glycidyl methacrylate, 20.0 to 30.0 parts of ethoxyethyl methacrylate, 1.0 to 3.5 parts of free radical photoinitiator, and 0.01 to 0.05 parts of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid; The acrylic modified epoxy resin is synthesized from methacrylic acid, difunctional glycidyl ether, triphenylphosphine and a polymerization inhibitor, and comprises the following steps: S1, adding methacrylic acid and difunctional glycidyl ether according to a preset molar ratio, and then adding triphenylphosphine and a polymerization inhibitor, and mixing them evenly; the preset molar ratio is (1.03-1.05):1; S2. Heat to 120-130°C under nitrogen and stirring conditions, react for 3-8 hours until the acid value of the product is ≤10 mgKOH / g, cool down, filter, and obtain acrylic acid-modified epoxy resin.
2. The UV-heat dual-curing electronic adhesive according to claim 1, characterized in that: Based on the total mass of methacrylic acid and difunctional glycidyl ether, the added amount of the triphenylphosphine is 0.3% to 0.35%, and the added amount of the polymerization inhibitor is 0.01% to 0.05%.
3. The UV-heat dual-curing electronic adhesive as claimed in claim 2, characterized in that: The difunctional glycidyl ether is at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A resin, 1,4-butanediol glycidyl ether, neopentyl glycol diglycidyl ether or 1,6-hexanediol diglycidyl ether.
4. The UV-heat dual-curing electronic adhesive as claimed in claim 2, characterized in that: The polymerization inhibitor is any one or more of hydroquinone, p-hydroxyanisole, p-benzoquinone or p-methylhydroquinone.
5. The UV-heat dual-curing electronic adhesive according to claim 1, characterized in that: The free radical photoinitiator is any one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide or ethyl 2,4,6-trimethylbenzoylphenylphosphonate.
6. The UV-heat dual-curing electronic adhesive as claimed in any one of claims 1 to 5, characterized in that: The infrared absorption spectrum of the acrylic modified epoxy resin has an absorption peak derived from the stretching vibration of a hydroxyl group, an absorption peak derived from the stretching vibration of a carbonyl group, an absorption peak derived from the stretching vibration of a vinyl group, and an absorption peak derived from the stretching vibration of an epoxy group.
7. The UV-heat dual-curing electronic adhesive as claimed in any one of claims 1 to 5, characterized in that: The number average molecular weight of the polymerized product of the electronic adhesive after ultraviolet light treatment is 2000-3000 g / mol.
8. A method for preparing a UV-heat dual-curing electronic adhesive as claimed in any one of claims 1 to 5, characterized in that: Add 45.0 to 65.0 parts of acrylic modified epoxy resin, 7.0 to 10.0 parts of N,N-dimethylallylamine, 3.0 to 5.0 parts of methacrylic acid, 5.0 to 10.0 parts of glycidyl methacrylate, 20.0 to 30.0 parts of ethoxyethyl methacrylate, 1.0 to 3.5 parts of free radical photoinitiator, and 0.01 to 0.05 parts of 2-(dodecyl trithiocarbonate)-2-methylpropionic acid into a container in sequence, mix well, and obtain the product.
Citation Information
Patent Citations
Preparation method of tri-functional resin and ultraviolet light and heating dual-curing adhesive
CN111205777A
Comb-type acrylic block copolymer and preparation method thereof
CN116063642A